Formation of the structure of microbiocenoses of soils of agroecosystems depending on trophic and hydrothermal factors - O. S. Demyanyuk; V. P. Patyka; О. V. Sherstoboeva; A. A. Bunas (Biosystems Diversity, 2018)
Ground soil, as the product primarily of the activity of microbiota, is under the permanent influence of ecological and anthropogenous factors. Soils are especially subject to pressure in agroecosystems, which increases due to the considerable fluctuation of climate system parameters. Using graph analysis, we have estimated the results of multiyear monitoring research on the functioning of microbiocenoses of three soil types in agroecosystems depending on the fertilizing and hydrothermal mode. It enabled us to detect peculiarities of formation of the structure soil microbiocenoses and to better understand ecologically important relations between functional groups of microorganisms in the soil depending on action of different factors. It has been determined that neither application of organic and mineral fertilizers into chernozem nor action of hydrothermal factors (temperature air and humidity) is a crucial characteristic of changing in the structure of its microbiocenosis. Microorganisms-producers of exopolysaccharides, which have a strong relationship with all trophic groups of microorganisms as they are their structural components, turned out to be the main block constructing factor, which is due to their strong influence on total content of microbal mass in soil. For soil of agroecosystems with dark-grey type of soil characteristic of content of total biomass of microorganisms is a basis for block constructing gremium, which affirms the state of microbiocenosis and processes occurring there under the action of researched biotic and abiotic factors. Microbiocenosis of sod-podzolic soil, unlike the other researched types of soils, reacted distinctly on applying of fertilizer and depended on the action of hydrothermal factors. Contrast in the range of hydrothermal regime caused a chaotic character of interaction between the basic characteristics in microbiocenosis of sod-podzolic soil with appearance of a direct and mediated relationship among them. Regardless of changes in hydrothermal factors , interactions between characteristics of total microbial mass content, eutrophic microorganisms, which use mineral and organic forms of nitrogen, and producers of exopolysaccharides were stable. It has been proved that estimating of ecological state of soil and influence of applicable agromeasures on it should be conducted according to the indices of total microorganism biomass content in the soil and correlation between the number of microorganisms which form the graph gremium.